(untitled) (Journal of Informatics Education and Research, 2023)
Ownership structure has been a prime variable in corporate governance literature. The structure of the ownership of corporate governance, influence the value of the firm. As proposed by agency theory, different ownership structure leads to varied level of managers’ motivation and engagement, which in turn leads to value creation. Using panel data for period 2011-2022 for a sample of listed firms in India, the study attempts to see a how the varied ownership structure influences the productivity of a firm - measured in terms of accounting performance measures while taking firm size, firm age, and leverage as control variable. Being multidimensional variable, the ownership is being analysed along the dimensions such as shareholders’ concentration, identity among others for its effects on the performance.